The Impact Of Corporate Social Responsibility Implementation Toward Company’s Productivity : A Case Study of Tourism Industries in Indonesia - Agustina, Eka Christine (Global and Policy Journal of International Relations, 2016)
ABSTRACTThe main purpose of this paper is to explore further the dynamic and debatable relationshipbetween corporate social responsibility (CSR) and economic performance of a company byanalyzing the impact to company productivity or economic growth. Many previous studies inthis topic mostly use the manufacturing or machine based related industries. However, fordeveloping countries like Indonesia, hospitality or service based industries contributessignificantly to the nation’s economic development rather than other industries. Apparently,tourism industries have a slightly different mechanism compare to other industries in order tomake the business sustainab le and CSR plays a very important tool for its development. Bylooking first from some definition about CSR, the paper will then discover some long ongoingdebate over CSR impact and divided it into two majors which are profit maximization andhuman resour ces management. The case will be taken from increasingly growing tourismindustry in Indonesia which it has been considered as the best practice of CSR due to its highawareness to environmental and society issue. The paper later found out that despite thereluctance of some company to fully implement CSR and sign some codes of conducts forcertain humanitarian issues, there is positive impacts especially toward the accountability ofworkers. Also, the so called branding impact of CSR action will bring pote ntial sustainabilityto the company despite some critics to its genuine purpose by company.Keywords:CSR implementation, economic performance, company productivity, tourismindustryDOI : https://doi.org/10.33005/jgp.v4i02.1915